Peran Hukum Kesehatan dalam Melindungi Peserta Program Badan Penyelenggara Jaminan Sosial Kesehatan Berdasarkan Undang-Undang Nomor 24 Tahun 2011 - Adella Sitanggang; Sonya Airini Batubara; Andre Widana Sahputra Sitepu; Erica Setiawan Tandi; F. Fitriani (Fakultas Hukum, Universitas Warmadewa, 2024)
The role of health law is crucial in ensuring the protection of participants in the National Health Insurance (BPJS Kesehatan) program, as regulated by Law No. 24 of 2011. This law provides a legal basis for the implementation of the national health insurance program, which aims to promote the welfare of society by providing equitable access to quality healthcare services. Health law functions to protect the rights of BPJS participants by ensuring that they receive healthcare services that meet established standards without discrimination.Furthermore, this law mandates the state to provide comprehensive and inclusive health insurance. Through the role of BPJS Kesehatan, health law also regulates the supervision and enforcement of accountability from healthcare providers, both in terms of service quality and financial management. Healthcare institutions collaborating with BPJS are required to comply with professional standards and medical ethics, as well as being responsible for patient safety.In the event of violations, health law provides a mechanism for participants to file complaints and seek justice through legal channels. The application of administrative and criminal sanctions for violators is also part of the legal protection efforts for participants. Therefore, the role of health law not only ensures access to services but also guarantees that the rights of BPJS participants are fulfilled in receiving fair and quality healthcare services.